Raising oil palm seedlings in urban cities using sole and amended woodash and sawdust manurial treatments - E. I., Moyin Jesu; E. F., Charles (Universiti Putra Malaysia Press, 2003)
A healthy seedling is a pre-requisite for a successful establishment of oil palm planting in the [wid. There were very limited soils available in the urban cities for raising of oil palm seedlings. Therefore, a study was conducted in Akure (Lat 7lN, 5'10'E) in the rainforest zone of South West Nigeria on the effectiveness of woodash and sawdust used ordinarily or in combination with goat, pig and poultry manure as fertilizers on the growth, leaf nutrients and soil chemical composition of oil palm (Elaies guineesis L) seedlings in the nursery. Eight organic fertilizer treatments were compared to the control (no fertilizer; no manure) and NPK 12:12:17 + Mg 2 fertilizer. The treatments were applied at 40 g per polybag filled with 10 kg soil (8t/ha), replicated three times and arranged in a complete randomized block design. The arganic fertilizers and soils were chemically analysed. The results showed that the application of arganic residues to the soil significantly increased (P<0.05) the soil and leaf N, P, K, Ca, Mg, Soil pH and O. M, plant height, stem girth and number of leaves of oil palm seedlings compared to the control treatment. Woodash + poultry manure and sawdust + poultry manure gave higher values of soil, leaf nutrients and growth parameters of oil palm seedlings than NPK + Mgfertilizer. Woodash + poultry manure increased the soil pH, O. M, N, P, K, Ca, Mg and Na lJy 14.8%, 328%, 75%, 51 %, 8.4%, 2546%,58% and 1123% respectively when compared to NPK + Mg fertilizer treatment. The woodash + poultry treatment increased the oil palm seedling leaf N, P, K, Ca and Mg nutrient contents lJy 3%, 38%, 20%, 266% and 200% respectively mare than NPK fertilizer while it also increased the leaf area, stem girth, number of leaf and shoot weight lJy 14 %, 22. 75 %, 17% and 57% respectively mare than the NPK + Mgfertilizer. However, NPK + Mgfertilizer gave better values of soil N, P, and K, plant height, leaf area, number of leaves and shoot weight than woodash and sawdust applied in sole farms while the arganic residues significantly increased (P<O. 05) soil and leaf Ca and Mg compared to the fertilizer. Woodash and sawdust applied solely ar amended at 8t/ha has been effective as sources offertilizer nutrients far raising oil palm seedlings.